V-VI դդ. հայկական բազիլիկ եկեղեցի Արարատի լանջին - Վահագն Գուրզադյան; Վարազդատ Հարությունյան (ՀՀ ԳԱԱ հրատ.)
В августе 2004 г. во время восхождения на Арарат по маршруту первовосходителей Паррота и Абовяна (1829 г.) В. Гурзадяном были сфотографированы развалины церкви (фото 1-3), находящейся на высоте 2100 м на северо-западном склоне горы Арарат. Церковь расположена в милитаризованной, строго охраняемой зоне, практически недоступной для иностранцев, куда В. Гурзадян (со спутником С. Аарсетом из Кембриджа) неожиданно получил особое разрешение. Недалеко от церкви, на вершине холма находятся развалины крепости (фото 4), а на склонах холма–развалины жилищ. Церковь построена из крупных блоков оранжеватого туфа. Сохранились остатки восточной абсиды церкви. In August 2004 while climbing Mt. Ararat by the route of the first-climbers Parrot and Abovian (1829), V. Gurzadyan took photos of a ruined church (photos 1-3 and others not represented here) situated at an altitude of 2100m in the north-west slope of the mountain. The church is located in militarized, carefully controlled zone, practically non-reachable for foreigners, where V. Gurzadyan (together with S.Aarseth of Cambridge) was granted unexpected exclusive entry permission. Ruins of a fortress (photo 4) are situated on the top of a nearby hill, while ruins of dwellings cover the latter’s slopes. The church is constructed of large blocks of orange tuff. Its eastern abside has survived better.
Keywords: History; D History; N Fine Arts; NA Architecture